The applying of the concept of individualization in sport - Kozina, Z.; Sobko, I.; Bazulyuk, T.; Ryepko, O.; Lachno, O.; Ilnitskaya, A. (Journal of Physical Education and Sport, 2015)
The aim is to summarize the impact results of the application of an individual approach on the level of special efficiency; to reveal the influence of an individual approach on the functional state of the sportsmen. Materials: There were 23 qualified basketball players, aged 20-22, involved in the research. Results: We have developed the theoretical conception of individualization of the training process. This concept lies in showing the leading factors in the individual structure of sportsmen` proficiency, in the analysis of regularities and prediction of individual dynamics of competitive results and in the development of universal methods of individualization of the training process. We also established that the use of individualization of sportsmen` training has positive effect on the autonomic balance and workability of sportsmen. Conclusions: The developed concept of individualization of the process of sportsmen` training helps to optimize the autonomic balance and to increase the sportsmen` workability.